Fungal Assemblages in Different Habitats in an Erman’s Birch Forest - Yang, Teng; Sun, Huaibo; Shen, Congcong; Chu, Haiyan (Frontiers in Microbiology, 2016)
Recent meta-analyses of fungal diversity using deeply sequenced marker genes suggest that most fungal taxa are locally distributed. However, little is known about the extent of overlap and niche partitions in total fungal communities or functional guilds within distinct habitats on a local forest scale. Here, we compared fungal communities in endosphere (leaf interior), phyllosphere (leaf interior and associated surface area) and soil samples from an Erman’s birch forest in Changbai Mountain, China. Community structures were significantly differentiated in terms of habitat, with soil having the highest fungal richness and phylogenetic diversity. Endophytic and phyllosphere fungi of Betula ermanii were more phylogenetically clustered compared with the corresponding soil fungi, indicating the ability of that host plants to filter and select their fungal partners. Furthermore, the majority of soil fungal taxa were soil specialists, while the dominant endosphere and phyllosphere taxa were aboveground generalists, with soil and plant foliage only sharing <8.2% fungal taxa. Most of the fungal taxa could be assigned to different functional guilds; however, the assigned guilds showed significant habitat specificity with variation in relative abundance. Collectively, the fungal assemblages in this Erman's birch forest were strictly niche specialized and constrained by weak migration among habitats. The findings suggest that phylogenetic relatedness and functional guilds’ assignment can effectively interpret the certain ecological processes.